Protein Content and Overrun Value of Ice Cream made from Cashew Nut Milk Substitution with the Addition of Sorghum Flour - Choirunnisa, Yumna; Kurnia, Pramudya; Sofyan, Aan; Wardana, Agung Setya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background : Ice cream is a frozen product made from milk, cream, and a combination of various other ingredients that are in great demand by the public. This ice cream research uses the basic ingredients of cashew nut milk with sorghum flour addition as a treatment. Objective : To determine the protein content and overrun value in cashew nut milk ice cream products with the addition of sorghum flour. Method : Experimental method with Completely Randomized Design (CRD). The independent variables are protein content and overrun value, while the dependent variable is the variation of the addition of sorghum flour with 2 replications and times analysis, respectively. Results : The protein content of cashew nut milk ice cream from the four treatments, the addition of 0% sorghum was 4.058%, the addition of 0.1% sorghum was 3.274%, the treatment of adding 0.2% sorghum was 3.816%, and the addition of 0.3% sorghum was 3.891%. There was no effect of protein content on the addition of sorghum flour (p=0.097) using the Kruskal Wallis test. The overrun value of cashew nut milk ice cream from the four treatments: the addition of 0% sorghum was 45.86%, the treatment of adding 0.1% sorghum was 39.56%, the treatment of adding 0.2% sorghum was 43.37%, and the addition of 0.3% sorghum treatment was 37.61%. There was an effect of the overrun value based on the four treatments (p=0.003) using the One Way Anova test followed by the DMRT test. There was a difference in the treatment of adding 0% sorghum with the addition of 0.1% and 0.3% and the addition of 0.3% and 0.2% sorghum. The protein content and overrun value have met the ice cream quality requirements in accordance with SNI 3713:2018. Conclusion : The highest protein content and overrun value were in the treatment of adding 0% sorghum and have met the ice cream quality requirements according to SNI 3713:2018.